2020
DOI: 10.3390/molecules25030742
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Stabilised Polymeric Mesoporous Silica Nanoparticles Improve Doxorubicin Efficiency: Tailored Cancer Therapy

Abstract: The fruition, commercialisation and clinical application combining nano-engineering, nanomedicine and material science for utilisation in drug delivery is becoming a reality. The successful integration of nanomaterial in nanotherapeutics requires their critical development to ensure physiological and biological compatibility. Mesoporous silica nanoparticles (MSNs) are attractive nanocarriers due to their biodegradable, biocompatible, and relative malleable porous frameworks that can be functionalized for enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 104 publications
(152 reference statements)
0
15
0
1
Order By: Relevance
“…Moreover, an increase in drug-binding affinity leads to an increase in stability and cellular internalization of the drug-loaded carriers in cancer cells [ 58 ]. For example, in one study, pegylated mesoporous silica NPs showed an enhanced DOX loading efficacy of 0.98 mg (DOX)/mg (MSN) [ 59 ], which facilitated the apoptosis in cancer cells. In another study, a composite of bioengineered silk, EMS2, and magnetic iron oxide (IO) NPs displayed more than two-fold higher DOX-loading capacity compared to plain EMS2 spheres, which catalyzed their potential as a DDS [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an increase in drug-binding affinity leads to an increase in stability and cellular internalization of the drug-loaded carriers in cancer cells [ 58 ]. For example, in one study, pegylated mesoporous silica NPs showed an enhanced DOX loading efficacy of 0.98 mg (DOX)/mg (MSN) [ 59 ], which facilitated the apoptosis in cancer cells. In another study, a composite of bioengineered silk, EMS2, and magnetic iron oxide (IO) NPs displayed more than two-fold higher DOX-loading capacity compared to plain EMS2 spheres, which catalyzed their potential as a DDS [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric micelles, including MSNs that have been coated with cross-linking organic and/or inorganic polymers or lipid bilayers that enclose drug that has been electrostatically loaded onto the MSN core. Moodley et al, 2020 described a polyelectrolyte coated MSN that combined organic and inorganic co-polymers grafted on to the superficial surface of the MSN creating a brush-like covering that showed pH-sensitive release of loaded drug [ 85 ].…”
Section: Controlled Gene and Drug Delivery Systemsmentioning
confidence: 99%
“…A polyelectrolyte coated MSN that showed pH-responsive drug release of 5-fluorouracil (5-FU) and doxorubicin, respectively in a cancer cell models was recently reported. It was concluded that the polymeric brush-coating of TPP, chitosan and PEG when protonated underwent a transformation, opening the MSN pores and releasing the drugs into the targeted cancer cells [ 85 , 110 ]. Yan et al, 2019 developed a MSN system capped with chitosan and folic acid for the pH-responsive release of both a chemotropic drug, DOX and a photosensitizer (pheophorbide a, PA) for targeted and synergistic cancer therapy [ 111 ].…”
Section: Controlled Gene and Drug Delivery Systemsmentioning
confidence: 99%
“…The systems discussed were selectively used for the delivery of anti- c-myc RNAi molecules. Nano-delivery systems such as mesoporous silica nanoparticles [ 100 , 101 ] and magnetic nanoparticles [ 102 , 103 ] are not discussed in this review, but showed potential in drug delivery, which can be considered for as future carriers of siRNA, shRNA, or DsiRNA.…”
Section: Anti- C-myc -Shrnamentioning
confidence: 99%